ANÁLISE ESPACIAL DA INFECÇÃO PELO VÍRUS DO DENGUE NO MUNICÍPIO DE GOIÂNIA. - MACIEL, Ivan José (2008)
Dengue is nowadays considered a growing public health problem worldwide. Several outbreaks of dengue have occurred in Brazil in the last two decades, and the country is now considered an endemic area where risk areas for sylvatic yellow fever also coexist. The current manuscript reviews the main epidemiological features of dengue in the world focusing in the peculiarities of the infection/disease progression in Brazil and, specifically, in Central-West Brazil. Some issues related to the challenge of control in the Central-West region and the opportunities for research are also discussed. In Brazil, the re-introduction of the vector (Aedes aegypti) dates 1976-77. The city of Rio de Janeiro (Southeast Brazil) was considered the starting point of viral dispersion to coastal and inland areas, since the first epidemic (DENV-1) in 1986. Brazil reports approximately 70% of the dengue cases in the Americas with the co-circulation of 3 dengue subtypes (DENV-1; DENV-2 and DENV-3). The disease affects mainly the adult population and the surveillance system has detected an increasing trend to hospitalization, disease severity and incidence in children and adolescents. Approximately 500,000 of dengue cases and 158 deaths were reported in 2007 compared to approximately 300,000 and 77 deaths in the previous year in Brazil. The first epidemic in Goiás State (Central-West Brazil) was reported in 1994. Nowadays the three serotypes co-circulate with high incidence rates and a large outbreak was reported in the city of Campo Grande (Mato Grosso do Sul State) (45,843 registered cases). The recent increase in cases related to sylvatic yellow fever, mainly in Goiás State, represents a public health warning related to vector surveillance and control.